Hegemonies of Language and Their Discontents : the Southwest North American Region Since 1540. - Vélez-Ibáñez, Carlos G. (University of Arizona Press, 2017)
The book provides a unique and broad look at the history, power, duality, and promise of Spanish and English in the U.S.-Mexico borderlands--Provided by publisher.